Active anti-roll bar control using electronic servo valve hydraulic damper on single unit heavy vehicle. Issue 11 (2016) - Vu, Van Tan; Sename, Olivier; Dugard, Luc; Gaspar, Peter
Abstract: Rollover is a very serious problem for heavy vehicle safety, which can result in large financial and environmental consequences. In order to improve roll stability, most of modern heavy vehicles are equipped with passive anti-roll bars to reduce roll motion during cornering or riding on uneven roads. This paper introduces the active anti-roll bars designed by finding an optimal control based on a linear quadratic regulator ( LQR ). Four electronic servo-valve hydraulic dampers are modelled and applied on a yaw-roll model of a single unit heavy vehicle. The control signal is the current entering the electronic servo-valve and the output of this actuator is the damping force generated by the hydraulic damper. Simulation results are obtained and compared in three different situations: without anti-roll bars, with passive anti-roll bars and with active anti-roll bars. It is shown that the use of two active (front and rear) anti-roll bars drastically improves the behaviour of the single unit heavy vehicle.